Development Trends of the Market of Agricultural Lending to Households in Ukraine: Analysis of Consumer and Mortgage Loans - Andros, Svitlana; Gerasymchuk, Vasyl (Research on World Agricultural Economy, 2023)
The purpose of the article is to assess the conditions and identify the features of the market for consumer and mortgage lending to households based on the economic and statistical analysis of the data panel. The instrumental and methodological apparatus of the article compiled general scientific principles and approaches to economic analysis: Scientific abstraction, analysis and synthesis, grouping, typology, comparison, qualitative and quantitative expert assessments; logical and contextual methods of processing theoretical material, as well as the method of economic and statistical comparisons. The article analyzes the dynamics of consumer and mortgage loans for households in Ukraine from 2007 to 2023, and highlights their socio-economic significance. The main problems in the field of consumer lending are formulated, the resolution of which is necessary for the intensive agricultural activity of households. It has been established that, despite the accumulation of certain experiences in the banking sector, the mortgage lending market has not become massive today. It is concluded that the reasons for this situation are the difficulty in the practical application of legislative regulations aimed at protecting the interests of creditors; high level of interest rates; low level of real income of households and, consequently, low effective demand for mortgage loans; the impossibility of mass provision of long-term mortgage loans due to high risk (interest, credit, legislative); almost complete exclusion of the state from participation in the formation of a civilized market for housing mortgage lending. The prerequisites for the further development of consumer and mortgage lending to households in Ukraine are formulated. The prospects for development and the main directions for improving consumer and mortgage lending to households are determined. ER